Protecting digital platform users by means of Private International Law - Pretelli, Ilaria (CUADERNOS DE DERECHO TRANSNACIONAL, 2021)
The present article offers perspectives on the possible adaptation of traditional connecting factors to the digital space. It analyses cases that pit platform users against each other and cases that pit platform users against the digital platform itself. For the first set of cases, reliable guidance is offered by the principle of effectiveness. The enforcement of court decisions in cyberspace is often necessary and also plainly sufficient to render justice. Enhanced protection of weaker parties is advocated, both in tortious (favor laesi) and contractual liability (protection of the weaker party), in line with the most recent achievements in human rights due diligence. Protection clauses leading to destination-based labour standards would be a welcome step forward. Protection of users also offers guidance for the shaping of private international law rules governing disputes between users and the platform.
Keywords: Connecting factors; Principle of Effectiveness; Favor Laesi; Tortious liability; Party autonomy; Consumer contracts; B2B relations; Digital platforms